Neotypification of the name Crocus biflorus Mill. (Iridaceae) and its consequences in the taxonomy of the genus - Harpke, Dörte; Kerndorff, Helmut; Pasche, Erich; Peruzzi, Lorenzo (Phytotaxa, 2016)
Recent phylogenetic investigations on the genus Crocus proved several infra-generic units predominantly within section Nudiscapus to be para- or polyphyletic even at infra-specific level. In particular, the 23 “subspecies” of C. biflorus Mill. turned out to be a polyphyletic assemblage grouping in very different clades and sub-groups. In addition, they were established under the binomial Crocus biflorus, not yet typified. As first step, we neotypified this name. Then, through a phylogeny based on the ETS region of the nuclear ribosomal (nr) DNA as an additional nuclear marker to the already available nrITS region, we further demonstrated that all the “subspecies” represent independent evolutionary lineages. Therefore, all these taxa are treated here at species level. To achieve this, 10 new combinations are proposed.